(untitled) (Fiep Bulletin - online, 2015)
I – Participation Invited as Secretary General of the FIEP (travels and lodging expenses paid by the Organizing Committee of the Seminar) I was able to take part in a Very Interesting International meeting where I collected a great deal of information.